2009
DOI: 10.1007/s12020-009-9195-x
|View full text |Cite
|
Sign up to set email alerts
|

GnRH receptor expression in human prostate cancer cells is affected by hormones and growth factors

Abstract: GnRH receptors (GnRH-R) have been found in various malignancies, including prostate cancer (PCa). They mediate the direct antitumor effects of GnRH analogs. Nevertheless, few reports concern drug-induced modulation of GnRH-R levels. In this study, we investigated GnRH-R expression in androgen-sensitive (LNCaP) and -insensitive (PC-3) PCa cells treated for 4 and 6 days with a GnRH agonist (Leuprorelin acetate, LA, 10(-11) or 10(-6) M), Dihydrotestosterone (DHT, 10(-9) M), Cyproterone acetate (CA, 10(-7) M), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…(Leuschner et al, 2003) In this study, Leuschner et al reported that DHT-dependent upregulation of GnRH receptor expression (up to 119%) in GnRH receptor positive prostate cancer cells was responsible for this hypersensitivity (Angelucci et al, 2009). Receptor upregulation was observed to the same extent when cells were treated with a GnRH agonist and DHT (Angelucci et al, 2009). The higher sensitivity of DU145 cells to glycolipopeptides and triptorelin is plausibly due to the increased number of GnRH receptors in the presence of DHT.…”
Section: Impact Of Sex Steroids On the Antiproliferative Activitymentioning
confidence: 62%
See 1 more Smart Citation
“…(Leuschner et al, 2003) In this study, Leuschner et al reported that DHT-dependent upregulation of GnRH receptor expression (up to 119%) in GnRH receptor positive prostate cancer cells was responsible for this hypersensitivity (Angelucci et al, 2009). Receptor upregulation was observed to the same extent when cells were treated with a GnRH agonist and DHT (Angelucci et al, 2009). The higher sensitivity of DU145 cells to glycolipopeptides and triptorelin is plausibly due to the increased number of GnRH receptors in the presence of DHT.…”
Section: Impact Of Sex Steroids On the Antiproliferative Activitymentioning
confidence: 62%
“…These results were consistent with previous reports that showed a steroid-dependent antiproliferative activity of GnRH agonists. (Leuschner et al, 2003) In this study, Leuschner et al reported that DHT-dependent upregulation of GnRH receptor expression (up to 119%) in GnRH receptor positive prostate cancer cells was responsible for this hypersensitivity (Angelucci et al, 2009). Receptor upregulation was observed to the same extent when cells were treated with a GnRH agonist and DHT (Angelucci et al, 2009).…”
Section: Impact Of Sex Steroids On the Antiproliferative Activitymentioning
confidence: 64%
“…In fact, antagonistic effects were observed on tumor cell growth as well as on the expression of PsA, MAP kinases, apoptosis-related genes and GnRH-R (22)(23)(24)(25)(26)(27)(28)(29). The molecular basis of the interference between DHT and LA is still unclear but conceivably could be ascribed to the analogue targeting of the androgen receptor (AR) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, GnRH agonists are ineffective in regulating cell growth when used alone, but they counteract or suppress the stimulation of cell proliferation induced by estrogens in mammary and endometrial cancer cells (22)(23)(24) and by androgens or epidermal growth factor (EGF) in CaP cells (25). In the same CaP cells, we demonstrated the ability of the GnRH agonist, leuprorelin acetate (LA), to modulate the expression of various genes and/or proteins correlated with growth, differentiation and apoptosis and to up-regulate GnRH-R (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…3 Some studies have elucidated a direct role for GnRH in prostate cancer cells. While there is still considerable debate, research indicates that GnRH agonist has antiproliferative effects on hormonesensitive and hormone-refractory human prostatic cancer cell lines.…”
Section: Gnrhr1 Silencing Blocks Antitumour Effect Of Gnrh Agonistmentioning
confidence: 99%